2012
DOI: 10.1155/2012/610160
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Surface Acoustic Wave Device with AlN Film on Polymer Substrate

Abstract: Surface acoustic wave device with c-axis-oriented aluminum nitride (AlN) piezoelectric thin films on polymer substrates can be potentially used for development of flexible sensors, flexible microfluidic applications, microsystems, and lab-on-chip systems. In this work, the AlN films have been successfully deposited on polymer substrates using the DC reactive magnetron-sputtering method at room temperature, and the XRD, SEM, and AFM methods reveal that low deposition pressure is beneficial to the highly c-axis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…At present, there are many theoretical and experimental studies using AlN SAWs and film bulk acoustic wave resonators for sensing applications (Hou et al 2012;Zhou et al 2012;Fu et al 2010b); however, little information is available on the microfluidic performance of the AlNbased SAW devices. This work demonstrates, for the first time, the microfluidic performance (including streaming, pumping, jetting and nebulization as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many theoretical and experimental studies using AlN SAWs and film bulk acoustic wave resonators for sensing applications (Hou et al 2012;Zhou et al 2012;Fu et al 2010b); however, little information is available on the microfluidic performance of the AlNbased SAW devices. This work demonstrates, for the first time, the microfluidic performance (including streaming, pumping, jetting and nebulization as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…37 They further fabricated AlN-based flexible SAW devices on PI substrate, with lamb waves and acoustic wave velocities up to 900010000 m/s. 67 Lamanna et al fabricated flexible and transparent AlN-based SAW devices on a PEN substrate using sputtering deposition. A large transmission-signal amplitude, up to ~20 dB, was achieved for the Lamb mode SAWs with an acoustic velocity of ~10,500 m s −1 .…”
Section: Aln Piezoelectric Filmmentioning
confidence: 99%
“…[79][80][81] In particular, Algieri et al reported deposition of a columnar of 0002-oriented AlN with a minimum RMS 6.32 nm on an area of 5 × 5 μm and a d 33 of 4.93 pm V −1 . [81] The first report of the SAW device based on PI/AlN was developed by Zhou et al [82] with a low transmission amplitude (<1db). Li et al recently developed a SAW device with AlN working at 4.95 GHz, improving the piezoelectric response (8.01 pm V −1 ) and reducing the roughness (3.2 nm) by adding a molybdenum interlayer of 200 nm.…”
Section: Processing Of Piezoelectric Materials For Polymeric Saw Devicesmentioning
confidence: 99%